Formation and structure of wood and phloem in Norway spruce - Gričar, Jožica (Les (Ljubljana), 2021)
Wood and phloem formation databases are important for understanding the effects of climate change and extreme weather events on species composition, tree vitality, wood production and wood quality in Slovenian forests. In this paper, we present the latest results on the radial growth of Norway spruce (Picea abies (L.) Karst.) at two sites in Slovenia, Panška reka (PAN - 400 m a. s .l.) and Menina planina (MEN - 1200 m a. s .l.) in 2009-2011. The focus was on the seasonal dynamics of early and latewood, and early and late phloem formation. We found that site conditions greatly affected the seasonal dynamics of wood and phloem formation, which was reflected in the width and structure of annual increments. At the higher elevation MEN site, the growing season was about a month shorter (about 4 months long), which resulted in 39% and 15% narrower wood and phloem increments, respectively. At MEN, the transition from early to latewood was observed on average only a week later than at PAN, while the transition from early to late phloem occurred on average 20 days later at MEN than at PAN. Information on the impact of site conditions on radial growth of spruce and wood quality is important for all stakeholders in the forest-wood value chain, as it can help to take appropriate management measures of adaptation to changing conditions.
Keywords: branike; cambium; early phloem; earlywood; growth ring; kambij; kasni floem; kasni les; late phloem; latewood; les; navadna smreka; Norway spruce; Picea abies; rani floem; rani les